SOME STRATEGIES TO SUCCESSFULLY LEARN AND MASTER EFL - Feliks Tans; Hilda M. Nalley (Postgraduate School, Universitas Nusa Cendana, 2022)
In this article, we argue that mastering a language or more than one language is something that can be successfully achieved by everyone in general, language students in particular, by implementing such strategies as: (1) learning harder; (2) problem-based learning; (3) having good imagination of your future; (4) regular and more intensive practices of English; (5) positive thinking; (6) keeping in touch regularly with great people; (7) writing, publishing, and speaking at academic meetings as often as possible; and, (8), last, but not least, being healthy by thinking well, having good food, having regular exercises, and trying not to smoke. By implementing, among other things, those strategies, language learners, we believe, can indeed be fluent in using the language(s) they are learning, including English as a foreign language (EFL) in the context of this article.